Estrategias de promoción turística para el balneario Los Cerritos ubicado en el Rcto. Calabí, cantón Quinsaloma - Leon Carranza, Lilia Katherine (2022)
The objective of this research work was to determine the importance of the implementation of strategies for the tourist promotion of the "Los Cerritos" Spa located in the Rcto. Calabí, Quinsaloma canton. For these reasons, in the following document an analysis was presented in order to promote tourism growth in the sector. This project was raised after the spa was recognized as a tourist attraction that attracts locals and foreigners; but at the same time it does not have advertising promotion strategies that attract more tourists. The methodology applied for the project consisted of exploratory research through the use of surveys, which allowed for a clearer approach to the subject. The results were shown through the development of cases that allowed observing the situations raised and detected; the same that allowed the author to conclude on the work investigated and recommend alternatives that promote the growth of tourism in the sector.